Efektifitas Shaker Exercise terhadap Disfagia pada Pasien Stroke: The Integrative Literature Review - Fransisca Winandari; Tri Wahyuni Ismoyowati; Candra Trilukita Nugraha; Lolita Elensari Wahyuning; Maria Raphelina Rosari (FORIKES, 2022)
Stroke is the presence of focal and global neurologic deficits, which can be severe and last for 24 hours or more and can result in death. According to the World Stroke Organization in 2018, in the world there are 13.7 million new cases every year and around 5.5 million deaths occur due to stroke. According to the Indonesian Ministry of Health in 2018, the prevalence of stroke in Indonesia at the age of >15 years was 10.9%. One of the clinical symptoms of stroke is dysphagia which occurs in 37-78% of stroke patients and if left untreated can cause complications such as aspiration and pneumonia. One of the exercises to overcome dysphagia is shaker exercise, which is an exercise that aims to train the suprahyoid muscles. The purpose of this study is to analyze previous research on shaker exercise on dysphagia in stroke patients. This study was an integrative literature review. The databases used were Google Scholar, Proquest, Pubmed, NCBI, Wiley, NIH, EBSCO, Portal Garuda, IJPMR, Springer, JIK, and Elsevier, with the keywords: